2006
DOI: 10.1086/501456
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Safety-Engineered Device Implementation in the Prevention of Percutaneous Injuries: A Review of Published Studies

Abstract: Nearly 6 years have passed since the Needlestick Safety and Prevention Act of 2000 was signed into law. We reviewed studies published since 1995 that evaluated the effect of safety-engineered device implementation on rates of percutaneous injury (PI) among health care workers. Criteria for inclusion of studies in the review were as follows: the intervention used to reduce PIs was a needleless system or a device with engineered sharps-injury protection, the outcome measurements included a PI rate, the intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 24 publications
1
40
0
3
Order By: Relevance
“…These devices reduce percutaneous injuries by 22% to 100%. 9,11 Some reduction is related to the efficacy of the intervention, whereas some is related to the number of percutaneous devices that can be completely replaced with safe alternatives. With ingenuity and effort, approximately 25% of general surgical procedures are candidates for completely sharpless technique, reverting to conventional sharp devices in less than 15%.…”
Section: Discussionmentioning
confidence: 99%
“…These devices reduce percutaneous injuries by 22% to 100%. 9,11 Some reduction is related to the efficacy of the intervention, whereas some is related to the number of percutaneous devices that can be completely replaced with safe alternatives. With ingenuity and effort, approximately 25% of general surgical procedures are candidates for completely sharpless technique, reverting to conventional sharp devices in less than 15%.…”
Section: Discussionmentioning
confidence: 99%
“…First, we found that 80% of the needle/lancet sticks occurred with non-safety devices. Considered in the context of earlier findings from this study-that the incidence rate of needle/lancet sticks was much lower 1) and the use of safety devices was much higher 7) in California compared to the U.S. as a whole-this suggests that, as with hospital health care workers [9][10][11] , increased use of safety devices by paramedics would reduce paramedics' risk of blood exposure. Furthermore, we reported previously that provision of safety devices by the employer was a major determinant of safety device use by paramedics 7) .…”
Section: Discussionmentioning
confidence: 55%
“…Needlestick injuries did decline at all three sites following the transition to SENs; however, a number of injuries continued to be reported. Ongoing injuries following the mandatory use of SENs have been described in a number of jurisdictions (Chambers et al 2015;Jagger et al 2010;Jagger and Perry 2003;Stringer et al 2011;WorkSafeBC 2011) and in studies of SEN efficacy (Lavoie et al 2014;Tuma and Sepkowitz 2006). As revealed in this study, there are a number of barriers to completely eliminating needlestick injuries under current conditions.…”
Section: Discussionmentioning
confidence: 78%
“…There was an expectation that the mandatory use of SENs could eliminate up to 90% of injuries in the province (Bill 1279(Bill 2005. Controlled studies that have examined the efficacy of SENs have documented considerable variation in outcomes (Lavoie et al 2014;Tuma and Sepkowitz 2006). Less-than-optimal outcomes have also been documented in other jurisdictions that have established regulatory standards to promote the adoption of SENs (Chambers et al 2015;Jagger et al 2008Jagger et al , 2010Stringer et al 2011).…”
Section: Résumémentioning
confidence: 99%